Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1523/jneurosci.0736-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Generation, Coordination, and Evolution of Neural Circuits for Vocal Communication

Abstract: In many species, vocal communication is essential for coordinating social behaviors including courtship, mating, parenting, rivalry, and alarm signaling. Effective communication requires accurate production, detection, and classification of signals, as well as selection of socially appropriate responses. Understanding how signals are generated and how acoustic signals are perceived is key to understanding the neurobiology of social behaviors. Here we review our long-standing research program focused on Xenopus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 124 publications
(200 reference statements)
0
37
0
Order By: Relevance
“…Social communication regulates major biological functions under strong selective pressure, such as finding reproductive partners, raising progeny, group coordination for territory advertisement, and protection from predators (Bradbury and Vehrencamp, 2011). It is not yet clear whether the mechanisms underlying these functions are conserved during evolution, but an increasing number of species has been studied to identify genes and brain circuits related to social interaction and communication (e.g., (Arriaga et al, 2012;Chen and Hong, 2018;Kelley et al, 2020;Tu et al, 2019)). Such knowledge on the phylogeny and ontogeny of social communication abilities is also clinically important to better understand the causes underlying neuropsychiatric conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Social communication regulates major biological functions under strong selective pressure, such as finding reproductive partners, raising progeny, group coordination for territory advertisement, and protection from predators (Bradbury and Vehrencamp, 2011). It is not yet clear whether the mechanisms underlying these functions are conserved during evolution, but an increasing number of species has been studied to identify genes and brain circuits related to social interaction and communication (e.g., (Arriaga et al, 2012;Chen and Hong, 2018;Kelley et al, 2020;Tu et al, 2019)). Such knowledge on the phylogeny and ontogeny of social communication abilities is also clinically important to better understand the causes underlying neuropsychiatric conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The genetic architecture of mating behaviors is understudied in anuran amphibians, with examples being largely limited to visual signals [ 114 , 115 ]. Information regarding the genetic basis of acoustic signaling and processing in frogs is even more scarce [ 116 ]. Nonetheless, insight can be gained from insects that exhibit temporal variation in elements of acoustic mating signals in a similar way to many frogs.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative trait mapping studies on Hawaiian crickets (genus Laupala ) have shown that candidate genes underlying temporal information in acoustic signals include genes encoding a cyclic nucleotide-gated ion channel, a calcium release-activated calcium channel, a signal peptide peptidase-like protein gene, a putative synaptic vesicle related protein [ 127 ], three of which fall within the bounds of synaptic transmission gene categories targeted in this study (Table 1 ). In frogs, [ 116 ], suggested that membrane currents of fast pulse rate neurons in the parabranchial nucleus of the brain are likely to mediate divergence of acoustic signals among Xenopus species and that these differences probably involve differential expression of ion channels. Though little is known about the genetic basis for species-specific acoustic differences, their ongoing work will examine gene expression differences within specific vocal and auditory neurons across this genus [ 116 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neuromodulators acting at select loci in neural circuits contribute to such plasticity in signal production. In frog ( Rhodes et al, 2007 ; Yu and Yamaguchi, 2010 ; Kelley et al, 2020 ) and bird vocal systems ( Wood et al, 2011 ), serotonin (5HT) is one such modulator. The organization of the serotonergic system is highly conserved among teleost fishes ( Lillesaar et al, 2007 ; Lillesaar, 2011 ; Lillesaar and Gaspar, 2019 ), and the widespread distribution of serotoninergic neurons in brains of this more ancestral vertebrate group suggests that 5HT may have played an important role in the evolution of neuroendocrine mechanisms regulating vertebrate communication behavior.…”
Section: Neuromodulatory and Hormonal Regulation Of Communication And Social Behaviormentioning
confidence: 99%